Association between leukocyte subpopulations and hematoma expansion after spontaneous intracerebral hemorrhage: A retrospective cohort study - Qin, Jiao; Wei, Haihua; Liu, Yuling; Du, Lixin; Xia, Jun (Frontiers in Neurology, 2022)
Abstract Aims: To verify the association between leukocyte subpopulations and hematoma expansion (HE) determined by two definitions in Chinese individuals who experienced spontaneous intracerebral hemorrhage. Methods: We enrolled 471 patients. The 1/2ABC formula was used to gauge hematoma volume. The outcome was whether HE appeared within 72 h. We used Definition1 (volume increase ≥ 6 mL or 33%) and Definition2 (volume increase ≥ 12.5 mL or 33%) to define HE, respectively. Binary logistic regression analysis was used to assess the association between leukocyte subpopulations and HE. For statistically significant leukocyte subpopulations, we also performed subgroup analyses to assess differences between subgroups. Results: Among 471 patients, 131 (27.81%) and 116 (24.63%) patients experienced HE based on Definition1 and Definition2, respectively. After adjusting for confounding factors, elevated monocyte count was associated with a higher risk of HE-Definition1 (adjusted odds ratio [aOR] 2.45, 95% confidence interval [CI] 1.02–5.88, P=0.0450) and HE-Definition2 (aOR 2.54, 95% CI 1.04–6.20, P=0.0399). Additionally, we compared the results before and after adjusting for coagulation parameters. Monocyte count was significantly correlated with HE only after adjusting for coagulation parameters. Increased neutrophil count was associated with a lower risk of HE-Definition1 (aOR 0.91, 95% CI 0.84–1.00, P=0.0463). No correlations were observed between lymphocyte and leukocyte counts and HE (P > 0.05), and no subgroup interactions were observed (interaction P > 0.05). Conclusion: A higher monocyte count is associated with a higher HE risk regardless of the two definitions, after excluding the influence of the coagulation parameters, which facilitates risk stratification. Moreover, an increased neutrophil count was associated with a decreased risk of HE in the context of HE-Definition 1, which reflects the importance of standardizing the definition of HE.